Musharakah Contract Implementation in the Financing of Shariah Newspaper Accounts: Hybrid Contract dalam Pembiayaan Rekening Koran Syariah (PRKS) - Nailus Sakinah; Miftahul Ikhsan, Muhammad; Herdiana, Nana; Setiawan, Iwan (Zona Law And Public Administration Indonesia, 2024)
Islamic banks have developed a number of new projects, including contracts in fiqh mu'amalah. Besides being accepted by Islamic banks, some fiqh mu'amalah contracts are modified to accommodate regional needs. Basically, the engineering of contracts in fiqh muamalah is one of the many innovative efforts that have been made by Islamic banks. This research is a literature review, which is a term for a research methodology that concentrates on collecting data from various sources. Academic books, research reports, and journal articles are examples of academic literature that serve as data sources in this research. The result of the research is Sharia Current Account Financing (PRKS) is a revolving working capital financing facility with the principle of musyarakah profit sharing with Line Facility. PRKS was developed to meet the needs of the community in its business operations. An important point in the PRKS mechanism is carried out based on a musyarakah contract. PRKS also allows the use of current accounts in accordance with the agreed customer business needs.